Solidaritas Kekerabatan Kelompok Tani Desa Tallu Bamba Kecamatan Enrekang Kabupaten Enrekang (Studi Budaya Sibalianan) - Alfiani Nurhijrah; Mrs. Nurlela; Mubarak Dahlan (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study examines the kinship solidarity of the yellow corn farmer group in Tallu Bamba Village in Enrekang Regency including the background of the formation of sibalianan culture, the function of sibalianan cultural solidarity, and the implications of sibalianan. This study uses a qualitative method, with as many as 12 informants. Collecting data using the method of observation, interviews and documentation. The results of this study indicate that the formation of sibalianan culture is due to the local community's initiative to help each other, especially yellow corn farmers. The reason for the community to maintain their culture is because as yellow corn farmers the work is quite heavy if done together it will make the work easier, so it is very important that each member of the farmer group continues to help each other. The function of solidarity among the community is very helpful among the farming community, namely a medium of communication for fellow farmers to exchange information about plant care, especially yellow corn, benefit from getting each other's turn to get help in carrying out sibalianan activities and connecting ties to the community even though no blood relation. In short, the people in Tallu Bamba Village work together to facilitate their work in carrying out agricultural activities.